I am really struggling to work out the limit of the following product:

$$ \lim_{n \to \infty} \prod_{1\leq k \leq n} \left (1+\frac{k}{n} \right)^{1/k}.$$

So far, I have spent most of my time looking at the log of the above expression. If we set the desired limit equal to $L$, I end up with:

$$\log L = \lim_{n\to \infty}\log\left(\frac{n+1}{n} \right)+\frac{1}{2}\log\left(\frac{n+2}{n} \right) +\cdots +\frac{1}{n}\log\left(\frac{n+n}{n} \right),$$

which I can simplify to: $$ \log L = \lim_{n\to \infty} \log(n+1)+\frac{1}{2}\log(n+2)+\cdots \frac{1}{n}\log(2n)-\log(n)\left(1+\frac{1}{2}+\cdots\frac{1}{n}\right). $$

I tried to consider the above expression in a different form with an integral, but was unable to arrive at anything useful.

I have been stuck on this for quite awhile now, and would appreciate any insight.



Hint, based on Surb:
$$ \log L = \lim_{n\to\infty} \sum_{k=1}^n\frac{1}{k}\log\left(1+\frac{k}{n}\right) =\frac{1}{n}\sum_{k=1}^n\frac{n}{k}\log\left(1+\frac{k}{n}\right) =\int_0^1\frac{\log(1+x)}{x}\;dx $$
by a Riemann sum argument.

| cite | improve this answer | |
  • 3
    $\begingroup$ The resulting integral is quite interesting and can be solved using the Taylor series for $\ln{(1+x)}$ to result in $$\sum_{n=1}^\infty\frac{(-1)^{n+1}}{n^2}=\frac{\pi^2}{12}$$ $\endgroup$ – Peter Foreman Jul 3 at 14:44

I thought that it would be instructive to present an approach that does not rely on Riemann Sums, but rather makes use of the Taylor Series of $\log(1+x)$. To that end, we proceed.

The function $\log(1+x)$ can be represented by its Taylor Series, $\log(1+x)=\sum_{\ell=1}\frac{(-1)^{\ell-1}}{\ell}x^\ell$ for $-1<x\le 1$. Using this representation, we can write

$$\begin{align} \sum_{k=1}^n\log\left(1+\frac kn\right)^{1/k}&=\sum_{k=1}^n\frac1k\log\left(1+\frac kn\right)\\\\ &=\sum_{k=1}^n\left(\frac1k \sum_{\ell=1}^\infty \frac{(-1)^{\ell-1}}{\ell}\left(\frac kn\right)^\ell\right)\\\\ &=\sum_{\ell=1}^\infty \frac{(-1)^{\ell-1}}{\ell n^\ell}\sum_{k=1}^nk^{\ell-1}\tag1 \end{align}$$

Next, noting that $\displaystyle \sum_{k=1}^n k^{\ell-1}=\frac{n^\ell}{\ell}+O\left(n^{\ell -1}\right)$, we have from $(1)$ that

$$\begin{align} \sum_{k=1}^n\log\left(1+\frac kn\right)^{1/k}&=\sum_{\ell=1}^\infty \frac{(-1)^{\ell-1}}{\ell^2 }+O\left(\frac1n\right)\tag2 \end{align}$$

Finally, letting $n\to \infty$ in $(2)$ yields the result

$$\bbox[5px,border:2px solid #C0A000]{\sum_{k=1}^\infty \log\left(1+\frac kn\right)^{1/k}=\sum_{k=1}^\infty \frac{(-1)^{k=1}}{k^2}}\tag3$$

The series on the left-hand side of $(3)$ is equal to $\frac{\pi^2}{12}$ (See This).

| cite | improve this answer | |
  • $\begingroup$ @will Please let me know how I can improve my answer. I really want to give you the best answer I can. $\endgroup$ – Mark Viola Jul 10 at 3:21


Taking logarithm, the product becomes

$$\frac 1n\sum_{k=1}^n\frac nk\ln(1+\frac kn)=$$

$$\frac 1n\sum_{k=1}^n\frac{\ln(1+\frac kn)}{\frac kn}$$

As a Riemann sum, the limit will be


This improper integral is convergent since $\lim_{x\to 0^+}\frac{\ln(1+x)}{x}=1$.

| cite | improve this answer | |
  • 2
    $\begingroup$ The integral is NOT improper! The integrand has a removeable discontinuity. $\endgroup$ – Mark Viola Jul 3 at 15:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.